2016
DOI: 10.1016/j.chemgeo.2016.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements concentrations and speciation in rainwater from Guiyang, an acid rain impacted zone of Southwest China

Abstract: Rare earth elements (REEs) and major ions were determined in rainwater samples collected from Guiyang in the acid rain impacted zone of Southwest China. The concentrations of total dissolved and acid-soluble REEs in rainwater are higher than those of most of the world's cities as well as the local surface water. The dissolved REE concentrations are negatively correlated to pH in rainwater. This is consistent with acidification of rainwater resulting in increasing REE concentrations. Speciation calculations usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…At a pH of 5.7, the pH of the rice growth medium, LnSO 4 + should be present as the main form of the REE interacting with the rice root. This is consistent with the results of Zhu et al (2016), who showed that LnSO 4 + is the dominant species within the pH range of 3.4 and 6.0 under similar solution conditions. The results of speciation calculations in Fig.…”
Section: Speciation Of the Ree With Fe(ii) Chloride Or Fe(ii) Sulfatesupporting
confidence: 93%
“…At a pH of 5.7, the pH of the rice growth medium, LnSO 4 + should be present as the main form of the REE interacting with the rice root. This is consistent with the results of Zhu et al (2016), who showed that LnSO 4 + is the dominant species within the pH range of 3.4 and 6.0 under similar solution conditions. The results of speciation calculations in Fig.…”
Section: Speciation Of the Ree With Fe(ii) Chloride Or Fe(ii) Sulfatesupporting
confidence: 93%
“…Considering the extremely low concentrations of REE+Y in rainwater (Zhang and Liu, 2004;Zhu et al, 2016), REE+Y are ultimately sourced from rocks which fluids move through. Studies have proposed a preferential leaching of REE-bearing solid phases to be a cause for the enrichment patterns (Sun et al, 2012a;Wallrich et al, 2020 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Areas with potential environmental problems include cities with large populations, extensive infrastructure, manufacturing industries, and sources of industrial waste (Dai et al 2016;Valdes et al 2013;Zhu et al 2016). Large cities are also influenced by factors related to the variety of geological materials and sedimentary deposits on which they are situated (Duplaya et al 2014;Radomskaya et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth elements (REEs) are of increasing scientific interest (Kabata-Pendias 2011; Liang et al 2014;Zhang et al 2013;Ladonin 2017;Moreira et al 2018;Wu et al 2018;Fabijańczyk et al 2019;Rzymski et al 2019;Elias et al 2019), especially concerning the application of lanthanides in classifying geological materials (Haskin et al 1966), describing and modeling different geological (Taylor and McLennan 1985) and industrial processes (Du and Turner 2015;Zhu et al 2016), and identifying mineral sources (Celo et al 2012;Censi et al 2017).…”
Section: Introductionmentioning
confidence: 99%